Proposição de um modelo de retroalimentação da gestão do processo de projeto a partir de medições de satisfação de clientes - Sampaio, Juliana Carvalho Schlachter (2010)
In research related to customer satisfaction, it has been observed that the collected data have not been systematically used in the feedback of the design process, despite the literature recommendations on the importance of incorporating these data. Moreover, especially when generating value for customers, the process of design affects the decisions taken at this stage impact continuously. Some research, seeking to manage customer needs, has assessed the use of decision making tools from the manufacturing industry to support the design process (eg,AHP, AD, TRIZ and QFD). Therefore, this exploratory research aims to propose a theoretical model through the integration of these tools, to assist both the feedback in the design process and value generation. Three methodological steps were conducted: analysis of the tolls used in the design process, adaptation of the tools for the construction requirements, and evaluation of the proposed theoretical model, which was obtained from literature research. A first version of the model was applied in a field research. Through four sources of evidence (pre-test, document research, focus groups and analysis of the model), the proposed model was refined and evaluated by designers through practical application in a supposedly real situation in the context of social interest housing promoted by the Brazilian Federal Government (PAR/CEF). It was concluded that the model can generate more value for the residents of this type of social interest housing; however, the applicability of the model in other contexts should be verified. The designers also found that the model shows the parameter of quality, but does not highlight the aspects related to cost. Finally, since some of the needs were not analyzed from the architectural point of view, the designers highlighted the importance of choosing the right prioritization criteria. In this sense, some of these assessments were incorporated into the third and final version of the model, while others are suggested as future work